Malikhaing pagsulat - dela Cruz, Mar Anthony S.; dela Cruz, Mar Anthony S.; Marquez, Servillano T. (USANT Sibs Publishing House Inc., 2017)
Pagsulat ng mailkling tula
Pagsulat ng tula at maikling kuwento -- Pagsulat ng dulang may isang yugto
Malikhaing pagsulat
bibliograpi
Tagalog
Keywords: Pagsulat